Soft exfoliation of 2D SnO with size-dependent optical properties. (8th June 2017) - Singh, Mandeep; Gaspera, Enrico Della; Ahmed, Taimur; Walia, Sumeet; Ramanathan, Rajesh; van Embden, Joel; Mayes, Edwin; Bansal, Vipul
Abstract: Two-dimensional (2D) materials have recently gained unprecedented attention as potential candidates for next-generation (opto)electronic devices due to their fascinating optical and electrical properties. Tin monoxide, SnO, is an important p -type semiconductor with applications across photocatalysis (water splitting) and electronics (transistors). However, despite its potential in several important technological applications, SnO remains underexplored in its 2D form. Here we present a soft exfoliation strategy to produce 2D SnO nanosheets with tunable optical and electrical properties. Our approach involves the initial synthesis of layered SnO microspheres, which are readily exfoliated through a low-power sonication step to form high quality SnO nanosheets. We demonstrate that the properties of 2D SnO are strongly dependent on its dimensions. As verified through optical absorption and photoluminescence studies, a strong size-dependent quantum confinement effect in 2D SnO leads to substantial variation in its optical and electrical properties. This results in a remarkable (>1 eV) band gap widening in atomically thin SnO. Through photoconductivity measurements, we further validate a strong correlation between the quantum-confined properties of 2D SnO and the selective photoresponse of atomically thin sheets in the high energy UV light. Such tunable semiconducting properties of 2D SnO could be exploited for a variety of applications including photocatalysis, photovoltaics and optoelectronics in general.